2016
DOI: 10.1681/asn.2016010019
|View full text |Cite
|
Sign up to set email alerts
|

The Survival Benefit of “Fistula First, Catheter Last” in Hemodialysis Is Primarily Due to Patient Factors

Abstract: Patients needing hemodialysis are advised to have arteriovenous fistulas rather than catheters because of significantly lower mortality rates. However, disparities in fistula placement raise the possibility that patient factors have a role in this apparent mortality benefit. We derived a cohort of 115,425 patients on incident hemodialysis ≥67 years old from the US Renal Data System with linked Medicare claims to identify the first predialysis vascular access placed. We compared mortality outcomes in patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
102
0
12

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(121 citation statements)
references
References 41 publications
7
102
0
12
Order By: Relevance
“…This finding adds to the recent studies by Quinn et al [2] and Brown et al [3] that propose a more nuanced view of the optimal care of patients with chronic kidney disease (CKD) stages 4 and 5. In these studies, patients who underwent an ultimately non-successful AVF placement and initiated dialysis with a hemodialysis catheter had improved mortality compared to those who had initiated dialysis with a catheter and had yet not undergone AVF construction.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…This finding adds to the recent studies by Quinn et al [2] and Brown et al [3] that propose a more nuanced view of the optimal care of patients with chronic kidney disease (CKD) stages 4 and 5. In these studies, patients who underwent an ultimately non-successful AVF placement and initiated dialysis with a hemodialysis catheter had improved mortality compared to those who had initiated dialysis with a catheter and had yet not undergone AVF construction.…”
supporting
confidence: 61%
“…The results of Quinn et al [2] and Brown et al [3] augment and complement the growing body of literature that demonstrates the benefits of pre-ESRD nephrology care, particularly in the form of an interdisciplinary CKD clinic. Pre-ESRD nephrology education using an interdisciplinary approach results in more patients beginning dialysis at home, and also leads to a greater percentage of patients with a permanent access when in-center hemodialysis is chosen [4] .…”
mentioning
confidence: 55%
“…Findings similar to our study were also reported recently by Brown et al, who showed that patients initiating hemodialysis with a TDC after failed AVF placement had significantly lower all-cause mortality rates than the TDC-only group, but higher mortality than patients initiating dialysis using an AVF. [24]…”
Section: Discussionmentioning
confidence: 99%
“…However, only 2.3% of deaths were access related; thus, the excess mortality in patients with catheters did not appear to be causally related to the catheters but may instead reflect underlying poor clinical status. In a USRDS study of 115,425 incident HD patients, Brown et al [41] reported that the group initiating dialysis with a catheter after a failed fistula placement had significantly lower mortality rates than the group who had a catheter placed first and used upon dialysis initiation (AHR 0.66, 95% CI 0.64-0.68). Thus, the actual mortality attributed to the catheter itself may be explained to a large degree by underlying patient factors.…”
Section: Discussionmentioning
confidence: 99%